2021
DOI: 10.1177/00033197211005206
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk Assessment Model Using Urinary System Contrast Blush Grading to Predict Contrast-Induced Acute Kidney Injury in Low-Risk Profile Patients

Abstract: Contrast-induced acute kidney injury (CI-AKI) can occur after coronary interventions despite protective measures. We evaluated the effect of urinary system contrast blush grading for predicting post-procedure CI-AKI in 486 patients with chronic coronary artery disease. Patient characteristics and blood samples were collected. Urinary system contrast blush grade was recorded during the coronary angiography and interventions. Post-procedure third to fourth day blood samples were collected for diagnosis of CI-AKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Several studies have indicated that worsened LVEF was a predictor of CI-AKI [ 23 26 ]. In accordance with the previous study [ 23 , 27 , 28 ], our study demonstrated that the age and basal creatinine were independently correlated with CI-AKI. Cinar T et al also indicated that the age, creatinine and ejection fraction score correlated with ST-elevation myocardial infarction-related cardiogenic shock [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have indicated that worsened LVEF was a predictor of CI-AKI [ 23 26 ]. In accordance with the previous study [ 23 , 27 , 28 ], our study demonstrated that the age and basal creatinine were independently correlated with CI-AKI. Cinar T et al also indicated that the age, creatinine and ejection fraction score correlated with ST-elevation myocardial infarction-related cardiogenic shock [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the continuation of efforts to develop clinically reliable risk stratification modalities, Ösken A et al [26] evaluated the neutrophil-to-lymphocyte ratio as a significant predictor of CI-AKI after carotid artery stenting with the adjusted odds ratio of 1.39 to 2.63 for CI-AKI. Similarly, another study by Efe SC et al [27] reported the urinary system contrast blush grading (grade 2 or higher) as an important predictor of CI-AKI along with elevated (>3.5) weight-adopted contrast medium ratio.…”
Section: Discussionmentioning
confidence: 74%
“… 2 , 3 Owing to the complexity of the mechanisms, effective preventative or therapeutic measures for PC-AKI are still lacking. 4 , 5 Therefore, the ability to estimate the risk of developing PC-AKI after PCI in a patient with STEMI may have great clinical importance in reducing the incidence of PC-AKI.…”
Section: Introductionmentioning
confidence: 99%